HUKUMAN REJAM, ZINA DAN KONTROVERSINYA: ANTARA ASPIRASI DAN REALITI DI NIGERIA: Stoning, Adultery and Controversies: Aspiration vs Reality in Nigeria - Mohamed Azmi, Norazlina; Ismail, Siti Zubaidah (Jurnal Syariah, 2014)
In countries that implement hudud, many sentences shocking to modern sensibilities have been imposed. One of the most controversial sentences is stoning to death provided for sexual offences particularly zina involving married (muhsan) offenders. Nigeria is one of the countries that has a mixed legal system where Shariah-based law and the civil laws can be operating inparallel. In certain states in the northern part, Shariah Penal Law was implemented after being re-introduced in 1999. The general aspiration is towards implementing the full theoretical component of Islamic criminal law comprising hudud, qisas and ta’zir within the country’s legal system. However, in reality, tensions, conflicts and controversies surrounded its implementation. This article evaluates how Nigeria has negotiated between the complexities of the law within the plural society and has tolerated the issue of what is seemingly seen as injustice for women, as most offenders convicted of zina and sentenced to stoning are women. Two most controversial cases were examined in order to establish whether the courts’ decision succeeded in reflecting Islamic justice.